TEACHING RUSSIAN LANGUAGE IN FOREIGN LANGUAGE GROUPS OF STUDENTS USING DIGITAL TECHNOLOGIES - Yunusova Nilufar Khamraevna (American Journals, 2024)
The article highlights the problems of using digital technologies that contribute to satisfying the development of linguistic, communicative and linguistic (cultural-linguistic) competencies of students.
Keywords: Digital infrastructure, Russian language, Russian literature, language competencies, motivation, training.